The History of Coquette Atheistic and Its Role in Modern Society - Chen, Changran (Transactions on Social Science, Education and Humanities Research, 2025)
The coquette atheistic is an intricate composition of hyper-feminine stylings, emerged prevalently in contemporary media spaces with increasing cultural significance. This research interrogates the coquette style through textual analysis of visual imagery, social media, and literary texts. In theoretical feminist frameworks, this research also explores how coquette fashion publicly reproduces, reclaims the feminine autonomy and voice, while resists the dominant patriarchal objectifying narratives. Involving themes of nostalgia, sexualization and girlhood, the study examines how coquette fashion operates as a coded language of identity and performance. By critically engaging with the aesthetics’ visual and textual components, this study seeks to illustrate how coquette style functions not merely as a fashionable look, but as a symbolic image where power, desire and indentity are presented. The findings suggests that even though the spreading of coquette risks reinforcing problematic gender archetypes according to its historical and literary precedents, it still demonstrates strong female empowerment. This study contributes to ongoing debates in fashion and media studies by revealing the fashion’s history, evolvement and influences.